Analisis Penerapan Pembiayaan Akad Murabahah Bank Rakyat Indonesia Syariah (BRI Syariah) Pekanbaru - Mohd Winario; Irawati Irawati; Hasgimianti Hasgimianti; Emilia Susanti (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2020)
This research was conducted at BRI Syariah Pekanbaru, with the aim of knowing the application of murabahah financing, is it in accordance with Islamic principles or is it in accordance with the fatwa set by DSN-MUI. The sampling method of this research using snowball sampling, by interview, observation and documentation. This research uses descriptive qualitative analysis. The results can be concluded that the application of BRI Syariah Pekanbaru murabaha financing uses a tiered percentage system from each year on the principal of murabahah financing. Determination of margins is still calculated based on the BI Rate and looking at the applicable margins in other banks. The murabahah financing system at the bank can start from administrative requirements, collateral requirements, financing conditions, financing ceiling, financing period, and fees charged to customers. In determining murabahah financing margins, the rate of inflation is still used annually. If the BI rate is higher, then the margin taken by the bank of the customers will be higher also.